Encyclopedia of International Higher Education Systems and Institutions - Teixeira, Pedro [Verfasser]; Shin, Jung Cheol [Verfasser] (Springer, 2018)
"This authoritative reference source covers all higher education themes in a comprehensive, accessible and comparative way. It maps the field for the twenty first century reflecting the massive changes that have occurred and the challenges ahead for future research. It provides a rich diversity of scholarly perspectives and covers the entire spectrum of higher education from a geographical, a topical and disciplinary perspective. It is unrivaled in its capacity to go beyond national boundaries and provides indispensible comparative analyses." (editor's abstract ; BIBB-Doku)
Keywords: S 1.4 Hochschulbildung; Erziehungswissenschaft; Hochschulbildung